Factors Associated with Abortion in Women of Reproductive Age - Ana Paula Vidal dos Santos; Edméia de Almeida Cardoso Coelho; Maria Enoy Neves Gusmão; Diorlene Oliveira da Silva; Patrícia Figueiredo Marques; Mariza Silva Almeida (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Abstract Purpose To verify sociodemographic factors associated with the occurrence of abortion in women of reproductive age, in areas covered by the Family Health Strategy (FHS), a program from the Brazilian Ministry of Health. Methods A cross-sectional study using household surveys of 350 women aged 15 to 49. The report of abortion was a variable indicator, and sociodemographic aspects were covariables. Prevalence ratio (PR) and respective 95% confidence intervals were used to estimate the magnitude of the associations. Results There were associations among age, civil status, race/color, and religion; an increase in the prevalence of lower levels of education, age less than 20, and student status were protective factors. Conclusion The association between sociodemographic characteristics and the report of abortion is attributed to the fact that there is a lack at the FHS in the availability of fundamental healthcare services for young women; these findings call for action to guarantee the access to information about contraceptives and guidance to decrease the risk of unplanned pregnancies and abortions.